An empirical examination of the role of financial conglomerates in the banking crisis of a recently liberalized developing country : the case of Jamaica - Langrin, R. Brian ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Estimates the determinants of the 1996/97 Jamaican banking crisis using survival analysis and conditionsl 'fixed effects' logit models. Examines the role of financial conglomerates in the Jamaican regulatory authorities' bank intervention decision.